2019
DOI: 10.6007/ijarbss/v9-i8/6221
|View full text |Cite
|
Sign up to set email alerts
|

Examining University Students’ Reading Performances and Behaviors with the Use of Eye-Trackers

Abstract: The primary aim of the study was to examine Malaysian students' reading behaviours and performances. A total of twenty-one participants took part in this study. Participants were segregated into two different reading proficiencies: high and low. Findings from the reading passage and comprehension questions are calculated and analysed. The high proficient readers initial processing time were much longer in reading passage as compared to reading comprehension question, while the low proficient readers had shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, there is a lack of studies conducted on participants from the young adult age group as demonstrated in the findings. Besides that, researchers can now be aware of how methodological variations can affect performance and in doing so re-evaluate or incorporate a more coherent and controlled approach such as eye-tracking (Hasrul, Hazita & Azizah, 2018;Sarah Yusri & Soh, 2019). Lastly, we have concluded the lack of studies done in Malaysia pens a huge gap in which more research can be done in order to fill in that gap.…”
Section: Resultsmentioning
confidence: 83%
“…Additionally, there is a lack of studies conducted on participants from the young adult age group as demonstrated in the findings. Besides that, researchers can now be aware of how methodological variations can affect performance and in doing so re-evaluate or incorporate a more coherent and controlled approach such as eye-tracking (Hasrul, Hazita & Azizah, 2018;Sarah Yusri & Soh, 2019). Lastly, we have concluded the lack of studies done in Malaysia pens a huge gap in which more research can be done in order to fill in that gap.…”
Section: Resultsmentioning
confidence: 83%